A comparative exposure assessment of foodborne, animal contact and waterborne transmission routes of Salmonella in Canada. (March 2020) - Christidis, Tanya; Hurst, Matt; Rudnick, Wallis; Pintar, Katarina D.M.; Pollari, Frank
Abstract: Salmonella is one of the leading causes of gastro-enteric disease in Canada, second only to Campylobacter . The mean exposure of Salmonella measured in cells ingested per person per day, from 15 transmission routes, including foodborne, animal contact and waterborne routes, was estimated for Canada using data inputs from 2005 to 2015. Chicken meat was estimated to have the highest exposure at 1.75E+00 cells/person/day. Other foodborne and waterborne transmission routes were roughly 3 log lower than the chicken meat exposure. Exposure at petting zoos and visiting a farm were at the bottom of the list at less than 1.00E-06 cells/person/day. Model output was most sensitive to the prevalence and concentration of contamination inputs, suggesting these are important areas for which more and better quality data need to be gathered. Chicken meat exposure exhibited no change when inputs modeled in a non log-linear manner, such as those related to cross-contamination and undercooking the food, were reduced by 10%. The results highlight the importance of chicken meat as an important route of exposure to Salmonella and provide further support for innovative efforts that advocate for public health interventions that reduce Canadians' exposure to Salmonella along foodborne, animal contact and waterborne transmission routes. Highlights: Fifteen Salmonella exposure routes were examined. Chicken meat was the most important Salmonella exposure source in Canada. Petting zoos, visiting a farm, and household pet exposures were the least important. Better prevalence and concentration data would improve many of the exposure models.